Penyuluhan dan pelatihan pembuatan pupuk organik cair berbahan dasar ikan rucah - Achmad Alifio Firdaus Ashari; Dona Wahyuning Laily (STAI Auliaurrasyidin Tembilahan, 2026)
Panimbang District is an area with a huge potential for marine nature. The increasing potential of the sea is balanced by the large number of rucah fish. The processing and utilization of rucah fish into liquid organic fertilizer independently is very good for business continuity and sustainability. The method of implementing the activity is carried out with offline activities including counseling and training. The activity was held on May 20, 2024 in Tanjungjaya Village with local community participants with counseling and training activities with BPP Panimbang. The results of the activity showed that many participants were enthusiastic about counseling and training activities on rucah fish processing innovations. Farmers hope that there will be many innovations provided by students and BPP related to the latest innovations that help the community in agricultural activities.